Impact of dry-wet and freeze-thaw events on pesticide mineralizing populations and their activity in wetland ecosystems: A microcosm study. (March 2016) - Vandermeeren, Pieter; Baken, Stijn; Vanderstukken, Ruben; Diels, Jan; Springael, Dirk
Abstract: Riparian wetlands are proposed to mitigate diffuse pollution of surface water by pesticides in agricultural landscapes. Wetland ecosystems though are highly dynamic environments and seasonal disturbances such as freezing and drying can affect microbial population sizes in the sediment and their functionality including pesticide biodegradation, which has hardly been studied. This study examined the effect of artificially induced dry-wet or freeze-thaw events on the mineralization of the pesticides isoproturon (IPU) and 2-methoxy-4-chlorophenoxy acetic acid (MCPA) in wetland microcosms, either without or with prior enrichment of IPU/MCPA degrading populations. Without prior enrichment, mineralization of IPU and MCPA was significantly reduced after exposure to especially freeze-thaw events, as evidenced by lower mineralization rates and longer lag times compared to non-exposed microcosms. However, herbicide mineralization kinetics correlated poorly with cell numbers of herbicide mineralizers as estimated by a most probable number (MPN) approach and the number of IPU and MCPA mineralizers was unexpectedly higher in freeze-thaw and dry-wet cycle exposed setups compared to the control setups. This suggested that the observed effects of season-bound disturbances were due to other mechanisms than decay of pesticide mineralizers. In addition, in systems in which the growth of pesticide mineralizing bacteria was stimulated by amendment of IPU and MCPA, exposure to a freeze-thaw or dry-wet event only marginally affected the herbicide mineralization kinetics. Our results show that season bound environmental disturbances can affect pesticide mineralization kinetics in wetlands but that this effect can depend on the history of pesticide applications. Highlights: Mineralization of the herbicides IPU and MCPA in wetlands was simulated in microcosms. Dry-wet and especially freeze-thaw events negatively affected the mineralization of IPU and MCPA under flooded conditions. IPU/MCPA mineralizing cells increased after the imposed changes implying that cell decay is not responsible for the effects. Prior exposure of the wetland community to the herbicides counteracted the effect of freeze-thaw events.